Exploring the best possible route of infection of verotxin producing escherichia coli in development of experimental gastroenteritis among streptomycin treated murine model - Mosharraf, Fahareen-Binta; Ahsan, Chowdhury Rafiqul; Nessa, Jamalun; Yasmin, Mahmuda (© 2015 Journal of Bangladesh Academy of Sciences, 2016)
This article was published in the Journal of Bangladesh Academy of Sciences [© 2015 ] and the The Journal's website is at: http://www.banglajol.info/index.php/JBAS/article/download/23658/16179.